Easy-to-biodegrade plastic bags made from food plant waste - Nurkanti, Mia; Novitasari, Dwi Rizki; Shik, Yula Birizqi (CV. Bimbingan Belajar Assyfa, 2023)
This research examines the development of biodegradable plastic bags made from specific types of food crop waste, such as [specific types of food crop waste], through a literature study from 2020 to 2024. This systematic literature review study aims to evaluate the effectiveness and sustainability of these plastic bags compared to conventional plastic bags. Using the Scopus database, this research identified around 50 articles from various countries discussing this topic. The analysis results show that the adoption of biodegradable plastic bag technology still needs to be improved, mainly due to the need for long-term research and comprehensive practical trials. The main challenges identified include the need for more data on biodegradation in various environmental conditions and the lack of information on production costs compared to conventional plastic bags. This research also highlights the need for more studies of long-term ecological impacts and a more detailed life cycle analysis, including [specific aspects of the life cycle analysis], to ensure the sustainability of these products. In addition, interest and research efforts in biodegradable plastics made from food crop waste increased significantly during the 2020-2024 period, indicating the great potential of this innovation in reducing plastic pollution and improving environmental sustainability. This research recommends more studies to address shortcomings and strengthen evidence regarding biodegradable plastic bags' effectiveness and long-term benefits. Overall, this research shows that despite significant challenges, the development of biodegradable plastic bags made from food crop waste has great potential to reduce the negative impact of conventional plastics on the environment. With further research and increased technology adoption, these plastic bags could become a sustainable solution to the global plastic pollution problem.